Right hippocampal contribution to visual memory: a presurgical and postsurgical study in patients with temporal lobe epilepsy. Issue 5 (1st November 1998) - Gleiβner, U; Helmstaedter, C; Elger, C E
Abstract : OBJECTIVES: Existing speculations regarding the cognitive functions of the right hippocampus suggest a special involvement in non-verbal memory functions. However, all supporting evidence in epileptic patients came from postoperative studies that did not consider the preoperative functioning level. The present study investigates in patients with right temporal lobe epilepsy (RTLE), both preoperatively and postoperatively, the role of the right hippocampus for visual memory, visuoconstruction, and spatial visualisation. METHODS: Two groups of patients with RTLE with and without right hippocampal damage (HC + /n=15 v HC − /n=13) were set up retrospectively thereby taking into account the surgical treatment (selective amygdalohippocampectomy v temporal resections sparing the hippocampus), the postoperative pathological findings (hippocampal sclerosis in the HC + group) and the seizure outcome (all seizure free). The two groups were compared with regard to their neuropsychological performance preoperatively and 3 months after temporal lobe surgery. RESULTS: The preoperative results indicated impaired visual memory performance only for the HC + patients, whereas the HC − patients exhibited no deficiencies in any of the assessed functions. Postoperatively, both groups exhibited partially improved performances. The type of surgical treatment had no different effects on the postoperative performance changes. CONCLUSIONS: The results suggest that hippocampal damage is the major cause of non-verbal memory deficiencies in preoperative patients with right temporal lobe epilepsy. Hence the results support and extend findings from previous postoperative studies. Right hippocampal resections did not increase the preoperative visual memory deficiencies, thus supporting the view that right temporal lobe resection in general bears only small risks for cognitve deteriorations.